DYNAMIC MECHANICAL BEHAVIOR AND CONSTITUTIVE MODEL OF FV520B MARTENSITIC PRECIPITATION-HARDENING STEEL - WU Liang; HU YiSen; JI Xiang; WANG Gang (Jixie qiangdu)
In order to obtain the dynamic mechanical properties of FV520 B martensitic precipitation-hardening steel,quasistatic and dynamic compression test of cylinder samples with different temperatures（ 20 ℃,100 ℃,300 ℃,500 ℃,700 ℃respectively） and strain rates( 0. 001 s-1,1000 s-1,3000 s-1,6000 s-1 respectively) were performed by Instron hydraulic testing machine and Split Hopkinson Pressure Bar（ SHPB）. Based on the Jonson-Cook and Power-Law constitutive model,the constitutive relation of material was fitted by the experiment results. The experiment results show that the yield stress and flow stress of material increase with the decrease of temperature. As the strain and strain rates increased,the yield stress increase at a certain temperature. The strain hardening effect,strain rate hardening effect and temperature effect were analyzed in this paper.It also can obtain that Power-Law model is more suited for FV520 B than Jonson-Cook model. The Power-Law constitutive model agrees well with the experimental results.